Pharmacognostical and Antibacterial Studies of Different Extracts of Euphorbia hirta L. - Ashwani Kumar, Bhuvaneshwar Upadhyay*, K.P. Singh and (Journal of Phytology, 2010)
SUMMARY Leaves of Euphorbia hirta, traditionally practiced in the treatments of boils, dysentery, enteritis and various skin conditions, were extracted by soxhlet extraction in various extraction mediums. The disc diffusion method was used to determine the antibacterial activity against many Gram positive and Gram negative bacteria (Standard strains and clinical isolates). Antibacterial sensitivity test indicated that the methanolic extract inhibited the growth of S. aureus, E. coli, and B. subtilis to varying extents while K. pneumonia was the most resistive strain to these extracts. Minimum inhibitory concentration (MIC), of the extract against E. coli, S aureus, and S. entertidis were in the range of 0.1mg/ml. Phytochemical analysis indicates presence of terpenes, tannins, alkaloids and flavonoids which might be accountable for its antimicrobial properties, and these results validate the traditional uses of the plant in the treatment of various diseases. <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Bhuvaneshwar Upadhyay et al. Pharmacognostical and Antibacterial Studies of Leaf Extracts of Euphorbia hirta L. J Phytol 2/6 (2010) 55-60